Elastic Wave Property of Concrete Decomposed by Steam Pressure Cracking Agent. (2022) - Kamiya, Osamu; Okuyama, Etsushi; Takahashi, Mamoru; Miyano, Yasuyuki; Ito, Shinichi; Murata, Kenji
No abstract available